Genetic Mapping of SSR Markers in Eight Soybean Chromosomes Based on F2 Population B3462 x B3293 - I Made Tasma; Ahmad Warsun; Dani Satyawan; Saptowo Jumali Pardal; Slamet Slamet (Jurnal AgroBiogen, 2011)
Genetic Mapping of SSR Markers in Eight SoybeanChromosomes Based on F2 Population B3462 x B3293. IMade Tasma, Ahmad Warsun, Dani Satyawan, SaptowoJ. Pardal, and Slamet. Aluminum toxicity is one of the maincontrains for cultivating soybean in acid soils. GeneticHak Cipta © 2011, BB-Biogenmapping of SSR markers is one step for detecting aluminumtoxicitytolerant QTLs in soybean. Another step is tophenotype the same population at various aluminum-toxicityenvironments. The objectives of this study were to analyzethe segregation of SSR markers in progenies of an F2population and map the markers in 8 soybean chromosomes.The F2 population was previously developed bycrossing the Al-tolerant parent B3462 and the Al-sensitiveparent B3293. Polymorphic SSR markers in the parents wereused to PCR amplify DNA of the 100 F2 progenies. PCRproducts were separated using agarose or polyacrylamidegels. A Chi-Square test was done with a null hypothesis thatprogenies segregated in a 1 : 2 : 1 ratio. Results showed that125 SSR markers were polymorphics in the parents. Out of125 polymorphic markers, 122 were segregated in theprogenies of the F2 population. Among the segregatingmarkers, 114 were segregated in a 1 : 2 : 1 ratio. Only 8markers (5.6%) did not follow the 1 : 2 : 1 ratio. One hundredand nineteen SSR markers were mapped in 8 soybeanchromosomes. These include 18 markers in chromosomeA2, 10 in B1, 16 (C1), 16 (F), 10 (G), 23 (J), 16 (L), and 10 (N).Total genetic maps covered was 1,194.8 cM with averagemap distances between two adjacent markers of 10.7 cM.Further SSR marker enrichment is required to fill in the gapsof several chromosomal regions. Genetic maps presented inthis study should be useful for detection of Al-toxicitytolerant QTLs in soybean.